CONTINUING PROFESSIONAL DEVELOPMENT FOR PHARMACISTS: PREFERENCES, INTERESTS AND EXPERIENCE - Stojkov, Svetlana; Arsić, Jasmina; Legetić, Branka; Jovanović Lješković, Nataša (Acta medicae Medianae, 2022)
One of the models of lifelong learning, Continuing Professional Development is a targeted, systematic, and tailored form of professional development. This paper aims to show the pharmacists' preferences, interests and experiences about models and areas of education.Moreover, a cross-sectional observational study was conducted through an online survey posted on the website of the Serbian Chamber of Pharmacy. Besides, a questionnaire was created with 11 questions for the purpose of the research. The survey was completed by 565 pharmacists, and 93.4% were employed by a community pharmacy. More than half of the respondents (56.7%) felt they needed to develop their professional competences. In addition, for most pharmacists surveyed, direct interaction with the lecturer was significant. Over two-thirds of the respondents showed the highest affinity for the "case report", labelling it as "the most interesting", followed by workshops and lectures. The most interesting were the education via the Internet (57.7%), where the digital choices available on the Internet with the possibility of automatic podcast download were the first choice among half of the respondents. When asked about participation in continuing education (CE) the previous year, pharmacists responded that 95% had participated in CE, of which nearly half were at more than 5 CE.According to the results of this research, the development of information technologies, the availability and diversity of educational content and models, the choice and active participation in education, were recognized by pharmacists in Serbia as an appropriate approach in professional development.
Keywords: pharmacist, pharmacy education, continuing professional development, continuing professional development for pharmacists